Mahathir CEO, Malaysia Inc. - Wong, Jean; Idrus Mohd Satna (Petaling Jaya : Asian Strategy & Leadership Institute, 1999)
The contents of Disk 1: The Man, The Nation, The New Paradigm, What Others Say, Speeches. Contents of Disk 2: Exclusive interview with Dato' Seri Dr. Mahathir Mohamad
Executive producer, Michael Yeoh
System requirements: 486 or higher processor, 16 MB RAM, Windows 3.1, 95 & Windows NT or later, Microsoft video for Windows, 640 X 480 display, 256 color or higher, 2 X speed CD-ROM or higher, 16 bit sound card
Keywords: Mahathir Mohamad, -- Tun, -- 1925- -- Biography